Response of paddy field cyanobacterium, Westiellopsis prolifica Janet to the inorganic nitrogenous fertilizers - Shamina, Mamiyil (Current Botany, 2021)
Cyanobacteria are prokaryotic nitrogen fixing microorganism which played a significant role in the nitrogen fixation and contributed much to the submerged rice cropping system of the world. It can luxuriantly flourish in paddy fields and providing nitrogen as well as various growth promoting substances that influence the growth of paddy plants. India, being an important rice producing country of the world, depends upon various inorganic fertilizers for rice cultivation. The heterocystous cyanobacterium, Westiellopsis prolifca is a common inhabitant in most of the paddy fields of Kerala. The growth and other biochemical parameters upon the growth of cyanobacterium were assayed. The nitrogenous fertilizer ammonium sulphate influences the chlorophyll-a synthesis, protein content and growth rate. But the ammonia excretion was drastically reduced in cyanobacterial cultures upon the treatment with inorganic fertilizers.